THE EFFECT OF TEACHING STRATEGIES AND SEL-EFFICACY ON STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION - Arthalina Romauli Sinaga; Rahmad Husein; Sri Minda Murni (LINGUISTIK TERAPAN, 2019)
The objective of this experimental research were to find out whether: (1) The students’ achievement in reading comprehension taught by using Annotation strategy was higher than that taught by using Compensation strategy, (2) the students’ achievement in reading comprehension with high self-efficacy was higher than that low self-efficacy, and (3) there was  interaction between teaching strategies and self-efficacy on the students’ achievement in reading comprehension. The population of this research was the students in grade IX of SMP Negeri 18 Medan of 2016/2017 academic year. There were 52 students as samples of this research by applying cluster random sampling technique. The instruments of this research were reading comprehension test and questionaire sheet. The data were analyzed using ANOVA at the level of significant α = 0.05. The result of the data analysis proved that:    (1) the students’ achievement in reading comprehension taught by using Annotation strategy was higher than that taught by using Compensation strategy, with Fobs (66.73) ˃ Ftab (4.10),  (2) the students’ achievement in reading comprehension with high self-efficacy was higher than that with low self-efficacy, with Fobs (94.83) ˃ Ftab (4.10),  (3) there was interaction between teaching strategies and self-efficacy, with Fobs (11.29) ˃ Ftab (4.10).     Keywords: teaching strategies, self-efficacy, reading comprehension